A Comparison of the Leaching Kinetics and Mechanism of Calcined Magnesite with an Organic Leach Reagent - Bakan, Feray; Lacin, Oral; Sarac, Hanifi (CHEM SOC PAKISTAN, 2016)
The leaching kinetics of calcined magnesite in aqueous lactic acid solutions was investigated in a batch reactor by using parameters such as temperature, acid concentration, particle size, solid/liquid ratio, and stirring speed. A mathematical model was evaluated for the rate increased by decreasing particle size and by increasing temperature; and initially the leaching is increased in terms of acid concentration and then decreased by increasing concentration. It was shown that the new mathematical model for calcined magnesite particle was: -1.9041.ln((1 - X-B)(1/3) + 1.157) + 0.952ln((1 - X-B)(2/3) - 1.1561(1 - X-B)(1/3) + 1.338 -3.298arctan(0.577(1.73(1 -X-B)(1/3) - 1)) = 3.b.k(S).C-A0/rho(B).R.t It was determined that experimental data complies with shrinking core model for fluid-solid systems. It was also found that the stirring speed did not change the dissolution and that the dissolution rate was controlled by surface chemical reaction. Additionally, the fact that leaching was controlled by the chemical reaction was also supported by the relationship between the rate constant and the particle radius. The activation energy of the process was determined to be 30.61 kJ mol(-1).
Keywords: Calcined Magnesite; Lactic acid; Leaching; Kinetics; Organic reagent; ACETIC-ACID SOLUTIONS; CALCAREOUS PHOSPHATE ROCK; DISSOLUTION KINETICS; NATURAL MAGNESITE; SULFURIC-ACID; LACTIC-ACID; ULEXITE; ORE; Chemistry